Aplikasi Teori Ida Jean Orlando dalam Asuhan Keperawatan pada Kasus Ansietas - Handayani, Fitri; Nursanti, Irna (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
This study explores the application of Ida Jean Orlando's Theory in nursing care for anxiety cases. It focuses on the discipline of the nursing process, highlighting the nurse's responsibilities, understanding patient behavior, immediate reactions, nursing actions, and patient health progress. The results indicate that the theory provides a relevant framework for enhancing nurse-patient interactions with strengths in sensitivity to patient needs. However, some criticisms regarding the structure and interpretation of patient behavior need addressing. This study offers valuable insights for the development of more effective nursing practices in addressing anxiety cases.